Security analysis of LNMNT-lightweight crypto hash function for IoT - Nabeel, Nubila; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (IEEE, 2021)
Conventional cryptographic techniques are inappropriate for resource-constrained applications in the Internet of Things (IoT) domain because of their high resources requirement. This paper introduces a new Lightweight (LWT) hash function termed Lightweight New Mersenne Number Transform (LNMNT) Hash function, suitable for many IoT applications. The proposed LWT hash function is evaluated in terms of randomness, confusion, diffusion, distribution of hash function, and different attacks. The randomness analysis is performed using the NIST test suit. The LNMNT LWT hash function has been benchmarked against other LWT hash functions in terms of execution time, cycles per byte, memory usage, and consumed energy. The analysis showed that the LNMNT LWT hash function has excellent randomness behavior and is highly sensitive to the slight change in the input message too. Moreover, it provides low execution time, memory usage, and power consumption against the other LWT hash functions.